Emergency department visits for ambulatory care sensitive conditions by persons with Rheumatoid Arthritis: A population-based study - Dani G. Contreras; Zanir Bhanji; J. Antonio Aviña-Zubieta; Claire E.H. Barber; Cheryl Barnabe (PLoS ONE, 2025)
Purpose We estimated emergency department (ED) visit rates for Canadian-indicator Ambulatory Care Sensitive Conditions (ACSCs) by persons with rheumatoid arthritis (RA) relative to age- and sex-matched general population controls. Methods Cases were identified using a validated definition based on International Classification of Diseases codes (years 2002–2023). We identified visits in the National Ambulatory Care Reporting System (NACRS) where the most responsible diagnosis was for any ACSC (grand mal seizures, chronic lower respiratory diseases, asthma, diabetes, heart failure and pulmonary edema, hypertension, angina) and extracted visit acuity. Annual incidence rates were calculated within five years from the index date. The incidence rate ratio between RA and non-RA was estimated using a multivariable regression model, adjusting for age, sex, location of residence, and socioeconomic status. Results RA (n = 35,770 individuals) had higher ED visit rates for all ACSCs combined compared to Non-RA (n = 94,094 individuals) (crude IRR 1.26, 95% CI 1.22, 1.31), persisting after adjusting for confounders (adjusted IRR 1.30, 95% CI 1.25, 1.34). More than two-thirds of ED visits for ACSCs were triaged as “urgent” or higher severity. Over the study period, there was a 34% increase in the proportion of ED visits for an ACSC condition among those with RA. Conclusion RA cases had a 30% higher rate of avoidable ED visits in the first 5 years following diagnosis compared to non-RA. Improved ambulatory care access and care quality, inclusive of primary care and subspecialty care, is proposed to reduce the burden on the acute care system.